MEDIAN LETHAL CONCENTRATION EKSTRAK DAUN MIMBA Azadirachta indica PADA ULAT GRAYAK (Spodoptera litura F.) SEBAGAI INDIKATOR BIOINSEKTISIDA - Tyas Nyonita Punjungsari (Universitas Islam Kadiri, 2022)
ABSTRACT This experiment was conducted to determine the effect of mimba (Azadirachta indica) leaf extract as an alternative natural insecticide to S. litura in terms of the median lethal concentration (LC50). The research method used was a completely randomized design (CRD), with three replications, each replication was treated by adding 4 doses of mimba (Azadirachta indica) leaf extract (5%, 10%, 20% and 40% ppm). Data were collected at 24, 48, 72, 96, 120, 144, and 168 hours. Data analysis used probit analysis with SPSS 23, 95% confidence level. The results obtained from the study were that to kill S. litura larvae within 24 hours required a concentration of 91.670% neem leaf extract, while the lowest concentration required to kill S. litura was 3.425% within 168 hours.